Clinical Profile and Etiology of Children Presenting with Prolonged Fever in a Tertiary Care Hospital - Nasrin, Evana; Ahammad, Forrukh; Afrin, Sonia (Medicine Today, 2025)
Introduction: Prolonged fever in children, defined as fever persisting for ≥10 days without an initially identifiable cause, is a common yet diagnostically challenging clinical presentation, especially in resource-limited settings. Aim of the study: To determine the common causes of prolonged fever and its clinical presentation and outcome which may guide to narrow the diagnostic approach. Materials and Methods: A prospective observational study was conducted on 86 children aged 1 year to 12 years admitted with prolonged fever. Detailed history, clinical examination, and a stepwise diagnostic protocol—including baseline and targeted investigations—were used to determine underlying causes. Result: The majority were aged between 5 to 10 years (43.02%), followed by 1–5 years (33.72%) and 10-12 years (23.25%). In terms of gender males are predominate (56.97%). The common identifiable causes were Rickettsial fever (31.40%), Leukemia& lymphoma (11.63%), Enteric Fever (10.46%) and Bronchopneumonia (10.46%). In 6.97% of cases, the cause of prolonged fever remained undiagnosed. The most common associated clinical features included chills or rigors (43.02%), Pallor (36.05%), hepatomegaly (26.74%), cough (23.25) and vomiting (20.93%). Categorization of the diseases showed infectious cause predominant (73.25%) then malignancy (13.95%) and connective tissue /autoimmune disease (5.81%). Most hospital stays ranged from 8 to 14 days (50.00%), during which 86.04% recovered, 11.62% were referred, and one death occurred. Conclusion: Infectious diseases remain the predominant cause of prolonged fever in children in low-resource settings. However, a notable proportion had non-infectious or undiagnosed etiologies, highlighting the need for a structured, multi-tiered diagnostic approach. Early recognition and context-specific management strategies are essential to improve outcomes. Medicine Today 2025, Vol.37 (2): 225-229